HUBUNGAN ANTARA OBESITAS, POLA MAKAN, DAN AKTIVITAS FISIK DENGAN TINGKAT HIPERTENSI PADA LANSIA DI POSYANDU SIDOMULYO - Rika Barotut Taqiyah; Rusnoto Rusnoto; Diana Tri Lestari (Yayasan Nusantara Hasana Berdikari, 2026)
Hypertension, or high blood pressure, is a chronic medical condition characterized by elevated arterial blood pressure. Understanding the factors influencing the development of hypertension in the elderly is crucial for identifying and developing better prevention and management strategies. Factors requiring further research include obesity, diet, and physical activity. The purpose of this study was to determine the relationship between obesity, diet, and physical activity with hypertension levels in the elderly at the Sidomulyo Integrated Health Post (Posyandu). The research method used correlational analysis with a cross-sectional design approach. The population in this study was 40 elderly residents of the Sidomulyo Integrated Health Post (Posyandu Sidomulyo), and the research sample was 36 respondents. The sampling technique used by researchers in this study is a Purposive Sampling technique. The inclusion criteria in this study are: active elderly at the Sidomulyo Integrated Health Post and willing to fill out the questionnaire completely. The exclusion criteria in this study are: elderly who are no longer active at the Sidomulyo Integrated Health Post and are not willing to be respondents. The instruments used are digital scales to measure body weight in determining obesity status, measurement of Eating Patterns using the Food Frequency Questionnaire (FFQ) questionnaire, measurement of physical activity using the International Physical Activity Questionnaire (IPAQ) questionnaire and measurement of Hypertension using a digital tensiometer / tensiometer and stethoscope. Based on the results of the analysis using the sperm rank test, there are analysis results on the obesity variable showing a Sig. (2-tailed) value = 0.013 which is smaller than the sig value = 0.05 and there is a positive correlation value r = 0.410. So it can be interpreted that there is a fairly strong relationship. On the diet variable shows a Sig. (2-tailed) value = 0.026 smaller than the sig value = 0.05 which means there is a significant relationship between the diet variable and the level of hypertension with a positive correlation value of r = 0.370 which means there is a very low relationship between the diet variable and the level of hypertension. While on the physical activity variable there is a sig value = 0.002 with a positive correlation value of r = 0.509 which means there is a strong significant relationship between the physical activity variable and the level of hypertension. The conclusion of this study is that there is a significant relationship in the three variables as evidenced by the three sig values. (2-tailed) ≤ 0.05.